Small Area Estimation Using Empirical Bayes Poisson Gamma on Adolescent Fertility Rate in Indonesia: Small Area Estimation Menggunakan Empirical Bayes Poisson Gamma pada Angka Fertilitas Remaja di Indonesia - Septianingsih, Putri; Wulansari, Ika Yuni (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2023)
High population growth is one of the main population problems facing Indonesia. One of the government's efforts to overcome this is by preventing adolescent fertility. The Adolescence Fertility Rate (AFR) produced by the IDHS is designed until provincial level, whereas the availability of AFR at the district/city level is needed as an indicator of regional development measurement. The purpose of this research is to produce an estimation of AFR at the district/city level in Indonesia and find out which auxiliary variables significantly influence it and evaluate the performance of the model in estimating AFR. The analytical method used is descriptive analysis to explain the characteristics of adolescent fertility and auxiliary variables and also direct estimation and the indirect estimation method using Small Area Estimation Empirical Bayes Poisson Gamma. The results showed that the number of villages, school facilities, health facilities, health workers, telephone lines and operators significantly affected the fertility of adolescents and the results of the SAE EB Poisson Gamma estimation were better than the direct estimation method. Suggestions proposed are the government need to increase attention to districts/cities that have AFR that is higher than the average AFR or National AFR and increase the number of school facilities and the number of health workers.